Participatory-based approach to safeguarding a festival's cultural significance : a case study of Salak Yom festival in Lamphun province, Thailand - Linina Phuttitarn (Chulalongkorn University, 2012)
Thesis (M.A.)--Chulalongkorn University, 2011